Employer Branding and Recruitment: Social Media Field Experiments Targeting Future Public Employees - Florian Keppeler; Ulf Papenfuß (Public Administration Review, 2021)
Public sector recruitment is an urgent and prevailing challenge in both research and practice. Public employer branding is an important subject in the theoretical debate, but the mechanisms behind how certain signals of public employers affect individuals' interest in a job are under-researched. By bridging signaling theory, social identity theory, and personnel economics, this study analyzes the effects of signals in advertisements related to societal impact, job security, and performance orientation on different gender/age-based target groups. This series of pre-registered social media field experiments (n~=~196,822 persons) with four public employers examines the degree to which these signals affect individuals' interest in a job at a public employer. The results do not show an overall impact of the signals but target group-specific effects—gender has a significant effect and age for certain public employers. Compared with the societal impact signal, the job security signal has a slightly stronger effect.
Keywords: 340